Estimation of dam sedimentation using remote sensing - Alias, Nor Asiken; Mansor, Shattri (2018)
This study outlines the estimation of dam sedimentation of the Batu Dam using remote sensing. The main objective of the study is to estimate and measure the storage capacity and sedimentation of Dam. The specific objectives of this study are to identify of water pixels and water spread area from Image of Surface reflectance Landsat 8 (OLI) data and to get the sedimentation rate by revise the capacity elevation curve and relate with original storage curve. The sedimentation estimation was carried out using satellite data, which are surface reflectance Landsat 8 data and dam water level data from 2013 to 2017 was used. Water spread area was analyzed from satellite of Landsat 8 data. The Normalized Difference Water Index (NDWI) has been used to delineate open water features and to enhance the presence of water surface in satellite imagery of the Batu Dam. Water spread area of the dam at a particular elevation on the date of the passing of the satellite was used to develop an elevation-area-curve. For this study, the linear interpolation/extrapolation technique has been engaged to measure the water spread area of Batu Dam at different elevations. Further, these areas were used to compute the live storage capacity of the dam between two elevations by the trapezoidal formula. From the study, it was found that the sediment volume since 1987 until 2017 the loss of capacity was 7.31 Mm3, which was the 23 percent loss from the original live storage capacity. Based on the Landsat 8 survey the annual sedimentation rate is 0.24 Mm3 per year and is equivalent to 0.8 percent per annum.